(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The bulk of Chronobiology International research articles describe results from studies on laboratory animals and humans. The editors and readers of the journal expect writers to have made significant contributions to biological rhythm and related research via ethical research and honest reporting of results. Scientific authors must declare any possible conflicts of interest. The journal exclusively accepts original articles that have not been published elsewhere, save as short abstracts. The journal and its editors encourage investigators to follow the principles of the World Medical Association’s Declaration of Helsinki and the Institute for Laboratory Animal Research’s Guide for the Care and Use of Laboratory Animals. Chronobiology International judges whether or not the research techniques used in a publication meet the criteria of good research practice. This article updates Chronobiology International’s ethical principles, standards, and processes for submissions including human and animal biological rhythm research, both in terms of quality chronobiology research and compassionate and ethical study on humans and animals.